AB0481 EFFICACY OF APREMILAST FOR THE TREATMENT OF GENITAL ULCERS ASSOCIATED WITH ACTIVE BEHÇET'S SYNDROME: A COMBINED ANALYSIS OF TWO RANDOMIZED CONTROLLED TRIALS. (2nd June 2020) - Hatemi, G.; Mahr, A.; Takeno, M.; Kim, D.; Melikoglu, M.; Cheng, S.; Mccue, S.; Richter, S.; Brunori, M.; Paris, M.; Chen, M.; Yazici, Y.
Abstract : Background: Behçet's syndrome is a chronic, multi-system inflammatory disorder characterized by painful, recurrent oral ulcers (OU) and genital ulcers (GU). 1 The GU associated with Behçet's syndrome can contribute to difficulties with sexual activity, walking, and sitting 2 ; may cause scarring 1 ; and may impair quality of life. 1, 2 Apremilast (APR), an oral phosphodiesterase 4 inhibitor, has demonstrated efficacy in the treatment of the OU associated with Behçet's syndrome in the phase III, randomized RELIEF study (BCT-002). 3 Objectives: To describe the efficacy of APR for the treatment of GU associated with active Behçet's syndrome in the RELIEF study and in a pooled data analysis of RELIEF and the phase II study. Methods: Adult patients (≥18 years of age) with active Behçet's syndrome and ≥3 OU at randomization or ≥2 OU at screening and randomization, without active major organ involvement, were randomized (1:1) to APR 30 mg twice daily or placebo (PBO). In RELIEF, clinical improvement in GU was assessed by evaluating the time to the first GU recurrence after loss of complete response, the mean number of GU in patients without GU at baseline, and the proportion of patients who were GU-free (complete response) at Week 12 (regardless of baseline GU status). A pooled analysis of patients in RELIEF and a randomized, phase II study 4 were conducted to assess achievement of GU complete response in patients with GU at baseline. In patients with GU complete response before Week 12, the median time to the first GU recurrence after loss of complete response was based on Kaplan-Meier estimates. The mean number of GU was summarized descriptively using data as observed. Between-group differences in the proportion of patients who were GU-free at Week 12 were analyzed by Cochran-Mantel-Haenszel test using non-responder imputation to handle missing data. Statistical tests were 2 sided (α=0.05). Results: A total of 207 patients were randomized and received ≥1 dose of study medication (APR: n=104; PBO: n=103). In all, 17 patients in the APR group and 17 in the PBO group had GU at baseline, with mean GU counts of 2.9 (APR) and 2.6 (PBO). Among patients with GU at baseline in RELIEF, 12/17 (70.6% [APR]) and 7/17 (41.2% [PBO]) achieved GU complete response at Week 12 ( P =0.110). The median time to first GU recurrence in these patients occurred earlier with PBO (6.1 weeks) vs. APR (not calculable). In the pooled analysis of RELIEF and the phase II study, a significantly greater proportion of patients with GU at baseline achieved GU complete response at Week 12 with APR vs. PBO (21/27 [77.8%] vs. 9/23 [39.1%]; P =0.011) (Figure 1 ). The proportion of patients who were GU-free was significantly greater with APR (92/104 [88.5%]) vs. PBO (72/101 [71.3%]), regardless of baseline number of GU ( P =0.002) (Figure 2 ). Conclusion: The number of patients with GU was low, but the totality of the data shows a favorable trend in the treatment effect of APR on GU. Greater proportions of APR-treated patients were GU-free at Week 12 vs. patients receiving PBO, and the time to the first GU recurrence occurred earlier with PBO vs. APR. References: [1]Kokturk A. Patholog Res Int. 2012;2012:690390. 2. Senusi A, et al. Orphanet J Rare Dis. 2015;10:117. 3. Hatemi G, et al. N Engl J Med. 2019;381:1918-1928. 4. Hatemi G, et al. N Engl J Med. 2015;372:1510-1518. Disclosure of Interests: Gulen Hatemi Grant/research support from: BMS, Celgene Corporation, Silk Road Therapeutics – grant/research support, Consultant of: Bayer, Eli Lilly – consultant, Speakers bureau: AbbVie, Mustafa Nevzat, Novartis, UCB – speaker, Alfred Mahr Consultant of: Celgene, Speakers bureau: Roche, Chugai, Mitsuhiro Takeno Speakers bureau: Esai, Tanabe-Mitsubishi – speaker; Celgene Corporation – advisory board, Doyoung Kim: None declared, Melike Melikoglu: None declared, Sue Cheng Employee of: Amgen Inc. – employment; Celgene Corporation – employment at the time of study conduct, Shannon McCue Employee of: Amgen Inc. – employment; Celgene Corporation – employment at the time of study conduct, Sven Richter Employee of: Amgen Inc. – employment; Celgene Corporation – employment at the time of study conduct, Michele Brunori Employee of: Amgen Inc. – employment; Celgene Corporation – employment at the time of study conduct, Maria Paris Employee of: Amgen Inc. – employment; Celgene Corporation – employment at the time of study conduct, Mindy Chen Employee of: Amgen Inc. – employment; Celgene Corporation – employment at the time of the conduct, Yusuf Yazici Consultant of: BMS, Celgene Corporation, Genentech, Sanofi – consultant, Consultant of: BMS, Celgene Corporation, Genentech, Sanofi – consultant